The Effect of Electronic Word Of Mouth, Viral Marketing, Halal Certification, and Brand Image on Purchase Decisions of Mixue Ice Cream & Tea - Aninda Nurul Hasanah; Olivia Barcelona Nasution (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
This study aims to determine the effect of electronic word of mouth, viral marketing, halal certification, and brand image on purchasing decisions of Mixue Ice Cream & Tea. The independent variables in this study consisted of electronic word of mouth, viral marketing, halal certification, and brand image as well as the decision to purchase Mixue Ice Cream & Tea as the dependent variable. This study used 365 respondents. Data collection was carried out in this study using a questionnaire distribution technique containing several statements and questions which were arranged systematically. With the data collection model, spread online questionnaires using the Google Form. The data sources used are primary and secondary data sources and use SmartPLS version 4 for data analysis. The results of this study indicate that electronic word of mouth, viral marketing, and halal certification have an influence on the decision to purchase Mixue Ice Cream & Tea. Meanwhile, brand image has no effect on purchasing decisions of Mixue Ice Cream & Tea.